Genetic variation in MAOA modulates ventromedial prefrontal circuitry mediating individual differences in human personality - Buckholtz, J W; Callicott, J H; Kolachana, B; Hariri, A R; Goldberg, T E; Genderson, M; Egan, M F; Mattay, V S; Weinberger, D R; Meyer-Lindenberg, A (Molecular psychiatry, 2008)
Little is known about neural mechanisms underlying human personality and temperament, despite their considerable importance as highly heritable risk mediators for somatic and psychiatric disorders. To identify these circuits, we used a combined genetic and imaging approach focused on Monoamine Oxidase A (MAOA), encoding a key enzyme for monoamine metabolism previously associated with temperament and antisocial behavior. Male carriers of a low-expressing genetic variant exhibited dysregulated amygdala activation and increased functional coupling with ventromedial prefrontal cortex (vmPFC). Stronger coupling predicted increased harm avoidance and decreased reward dependence scores, suggesting that this circuitry mediates a part of the association of MAOA with these traits. We utilized path analysis to parse the effective connectivity within this system, and provide evidence that vmPFC regulates amygdala indirectly by influencing rostral cingulate cortex function. Our data implicate a neural circuit for variation in human personality under genetic control, provide an anatomically consistent mechanism for vmPFC–amygdala interactions underlying this variation, and suggest a role for vmPFC as a superordinate regulatory area for emotional arousal and social behavior.